Domain wall pinning through nanoscale interfacial Dzyaloshinskii-Moriya interaction - Kumar, Durgesh (2022)
Neuromorphic computing (NC) has been gaining attention as a potential candidate for artificial intelligence. The building blocks for NC are neurons and synapses. Research studies have indicated that domain wall (DW) devices are one of the most energy-efficient contenders for realizing NC. Moreover, synaptic functions can be achieved by obtaining multi-resistance states in DW devices. However, in DW devices with no artificial pinning, it is difficult to control the DW position, and hence achieving multilevel resistance is difficult. Here, we have proposed the concept of nanoscale interfacial Dzyaloshinskii-Moriya interaction (iDMI) for controllably stopping the DWs at specific positions, and hence, realizing multi-resistance states. We show that the nanoscale iDMI forms an energy barrier (well), which can controllably pin the DWs at the pinning sites. Moreover, a tunable depinning current density was achieved by changing the width and iDMI constant of the confinement region. We have also studied pinning in a device with five successive pinning sites. This feature is a proof-of-concept for realizing multi-resistance states in the proposed concept. Based on these observations, a magnetic tunnel junction - where the free layer is made up of the proposed concept - can be fabricated to achieve synapses for NC applications.